ANALISIS YURIDIS TERHADAP PERLINDUNGAN LINGKUNGAN HIDUP DALAM KEBIJAKAN INVESTASI PASCA BERLAKUNYA OMNIBUS LAW - Darmawan, Indira Nindya Savira (Universitas Labuhanbatu, 2025)
The investment climate in a country is influenced by the laws and regulations in force in that country. The Indonesian government is also trying to improve the investment climate in the country, one of which is by implementing new regulations that are deliberately made to replace previous regulations (Omnibus Law). This is marked by the issuance of Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law (Job Creation Law). This law aims to facilitate business activities in Indonesia. After the issuance of the Job Creation Law, which also includes the elimination, amendments, and new regulations of several articles in Law No. 32 of 2009 concerning Environmental Protection and Management (UUPPLH), the business licensing process must still pay attention to environmental impacts. This study uses a normative juridical method, namely research based on literature studies and secondary data. The results of the study indicate that changes related to the Amdal and Environmental Permit which were replaced with Environmental Approval need to be corrected, because it is feared that it could cause environmental damage in the future.Keywords: Environment; Investment; Omnibus Law; Job Creation